2016
DOI: 10.1080/23723556.2015.1061097
|View full text |Cite
|
Sign up to set email alerts
|

p32: A new player in autophagy

Abstract: Unc-51 like kinase-1 (Ulk1) is essential for autophagy induction. We recently reported that p32/C1QBP is crucial for the induction of autophagic flux upon starvation and the clearance of damaged mitochondria through the regulation of Ulk1 stability and kinase activity. Our results underscore the importance of p32 in fine-tuning the stress response and mitochondrial homeostasis via Ulk1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Meanwhile, this study showed that PCV2 Cap act as a predominant regulator to promote porcine cGAS phosphorylation and HDAC6 activation through mediating PI3K/AKT and PKCδ signaling activation. Importantly, PCV2 Cap-binding protein gC1qR (also known as C1QBP/gC1qR/HABP1/p32), a multiligand-binding and multifunctional protein [ 56 , 57 ], is also a crucial regulator for the activation of HDAC6 and HDAC6/autophagy-mediated cGAS degradation in PCV2-infected cells. Taken together, these data demonstrated that PCV2 infection activates the gC1qR/HDAC6/autophagy regulator axis to promote cGAS degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, this study showed that PCV2 Cap act as a predominant regulator to promote porcine cGAS phosphorylation and HDAC6 activation through mediating PI3K/AKT and PKCδ signaling activation. Importantly, PCV2 Cap-binding protein gC1qR (also known as C1QBP/gC1qR/HABP1/p32), a multiligand-binding and multifunctional protein [ 56 , 57 ], is also a crucial regulator for the activation of HDAC6 and HDAC6/autophagy-mediated cGAS degradation in PCV2-infected cells. Taken together, these data demonstrated that PCV2 infection activates the gC1qR/HDAC6/autophagy regulator axis to promote cGAS degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, understanding how C1QBP orchestrates mitophagy to maintain mitochondrial homeostasis could provide critical insights. Jiao et al (2015) reported that C1QBP controlled mitochondrial autophagy to help cells adapt better to the challenging microenvironment (Jiao and You, 2016). Serine/ threonine kinase Unc-51-like kinase-1 (ULK1) is crucial in inducing mitophagy.…”
Section: Complement C1q Binding Protein Is Responsible For Mitochondr...mentioning
confidence: 99%
“… Jiao et al (2015) reported that C1QBP controlled mitochondrial autophagy to help cells adapt better to the challenging microenvironment ( Jiao and You, 2016 ). Serine/threonine kinase Unc-51-like kinase-1 (ULK1) is crucial in inducing mitophagy.…”
Section: Complement C1q Binding Protein Modulation Of Mitochondrial P...mentioning
confidence: 99%
See 1 more Smart Citation
“…Complement C11 binding protein (C1QBP, also named p32 and HABP1) is a multifunctional protein which plays a pivotal role in diverse cellular processes such autophagy and cell apoptosis 7 , 8 . It has been reported that C1QBP is mainly localized in the mitochondrial matrix and is less expressed in the cytoplasm, nucleus and on the cell surface 9 - 11 .…”
Section: Introductionmentioning
confidence: 99%